Biocompatible and Biodegradable Ultrafine Nanoparticles of Poly(Methyl Methacrylate-co-Methacrylic Acid) Prepared via Semicontinuous Heterophase Polymerization: Kinetics and Product Characterization - Henned Saade; María de Lourdes Guillén; Judith Cabello Romero; Jesús Cepeda; Anna Ilyna; Salvador Fernández; Francisco Javier Enríquez-Medrano; Raúl Guillermo López (International Journal of Polymer Science)
Ultrafine nanoparticles, less than 10 nm in mean diameter, of the FDA approved copolymer methyl methacrylate- (MMA-) co-methacrylic acid (MAA), 2/1 (mol/mol), were prepared. The method used for the preparation of these particles stabilized in a latex containing around 11% solids includes the dosing of the monomers mixture on a micellar solution preserving monomer starved conditions. It is thought that the operation at these conditions combined with the hydrophilicity of MMA and MAA units favors the formation of ultrafine particles; the propagation reaction carried out within so small compartments renders copolymer chains rich in syndiotactic units very likely as consequence of the restricted movements of the end propagation of the chains. Because of their biocompatibility and biodegradability as well as their extremely small size these nanoparticles could be used as vehicles for improved drug delivery in the treatment of chronic-degenerative diseases.